2023
DOI: 10.1038/s41598-023-33016-2
|View full text |Cite
|
Sign up to set email alerts
|

The hyperexcitability of laterodorsal tegmentum cholinergic neurons accompanies adverse behavioral and cognitive outcomes of prenatal stress

Abstract: Exposure to prenatal stress (PS) leads to the offspring's vulnerability towards the development of cognitive and behavioral disorders. Laterodorsal tegmentum (LDT) is a part of the brainstem cholinergic system that is believed to play a pivotal role in the stress-associated progression of anxiety, memory impairment, and addictive behaviors. In this study, we aimed to investigate the electrophysiological alterations of LDT cholinergic neurons and its accompanied behavioral and cognitive outcomes in the offsprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…Our findings also demonstrated that the offspring born to PS‐exposed dams demonstrated an impaired passive avoidance memory, as observed in the shuttle box test. This finding is in line with our previous observations that PS might contribute to adverse cognitive alterations in the newborn (Nazeri et al., 2015; Shabani et al., 2023). We further showed that agmatine improved memory impairment caused by PS in the male offspring.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings also demonstrated that the offspring born to PS‐exposed dams demonstrated an impaired passive avoidance memory, as observed in the shuttle box test. This finding is in line with our previous observations that PS might contribute to adverse cognitive alterations in the newborn (Nazeri et al., 2015; Shabani et al., 2023). We further showed that agmatine improved memory impairment caused by PS in the male offspring.…”
Section: Discussionsupporting
confidence: 93%
“…Mice were placed in the experiment room for at least 1 h before the start of the experiment. A previously established method using a communication stress box was employed to expose pregnant animals with physical or psychological stress (Shabani et al., 2023). The communication stress box is a cylinder (50 cm height × 50 cm diameter) containing 5 + 4 cells (nine cells in total).…”
Section: Methodsmentioning
confidence: 99%